The effect of gender in binge eating behavior in Chinese culture: the serial mediation model of body dissatisfaction and self-acceptance - Li, Chunlu; Lyu, Shuhui; Yan, Jimin; Meng, Xiaolu (Frontiers in Psychology, 2023)
The gender difference of binge eating behavior been highlighted by previous studies. However, psychological mechanisms underlying the gender difference of binge eating behavior remain unclear. This study addressed this issue from a sociocultural perspective. Firstly, we investigated the mediation effect of body dissatisfaction on the gender difference of binge eating behavior. Secondly, we examine the serial mediating role of body dissatisfaction and self-acceptance in gender differences of binge eating behavior. Here, we analyzed data from 703 Chinese university students using SPSS 26.0 and SPSS PROCESS. Results indicated that in Chinese culture, body dissatisfaction and self-acceptance independently or through a serial way mediate the gender differences in binge eating behaviors. At the end, we discussed the implications and limitations of the present study.